2013
DOI: 10.1007/s12011-013-9815-4
|View full text |Cite
|
Sign up to set email alerts
|

Lithium in the Public Water Supply and Suicide Mortality in Greece

Abstract: The purpose of the present study was to evaluate the association between lithium levels in the public water supply and prefecture-based suicide rates in Greece. Analyses were conducted with respect to lithium levels in 149 samples from 34 prefectures of Greece. The average lithium level was 11.10 μg/l (range 0.1 to 121 μg/l). The results indicate that there is a tendency for lower suicide rates in the prefectures with high levels of lithium in drinking water. Ecological studies explained by researchers Schrauz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 15 publications
3
43
1
5
Order By: Relevance
“…A nationwide Austrian study found an inverse association between lithium levels in drinking water and suicide rates after adjustment of population density, per capita income, proportion of Roman Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/jad Catholics, as well as the availability of mental health service providers (Kapusta et al, 2011). Furthermore, two recent studies, one conducted in Aomori prefecture of Japan (Sugawara et al, 2013) and the other in 34 province of Greece (Giotakos et al, 2013) also reconfirmed the inverse association between lithium levels in drinking water and suicide rates.…”
Section: Introductionmentioning
confidence: 99%
“…A nationwide Austrian study found an inverse association between lithium levels in drinking water and suicide rates after adjustment of population density, per capita income, proportion of Roman Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/jad Catholics, as well as the availability of mental health service providers (Kapusta et al, 2011). Furthermore, two recent studies, one conducted in Aomori prefecture of Japan (Sugawara et al, 2013) and the other in 34 province of Greece (Giotakos et al, 2013) also reconfirmed the inverse association between lithium levels in drinking water and suicide rates.…”
Section: Introductionmentioning
confidence: 99%
“…Die Resultate stimmen mit zuletzt zunehmenden ökologischen Studien aus Texas [4,5], Japan [6,30], Österreich [7] und Griechenland [8] überein, die nachweisen konnten, dass Lithiumvorkommen in der Umwelt -speziell im Trinkwasser -mit einer niedrigeren Suizidmortalität assoziiert sind.…”
Section: Diskussionunclassified
“…Zuletzt gab es mehrere Berichte über ein inverses Verhältnis zwischen Lithiumkonzentrationen im Trinkwasser und Suizidraten. Solche Ergebnisse wurden für Texas [4,5], Japan [6], Österreich [7] und Griechenland [8] gezeigt. Eine Studie in OstEngland zeigte jedoch keine solche Assoziation [9].…”
Section: Introductionunclassified
“…ecently, a series of ecological studies [1][2][3][4][5][6][7] on antisuicidal properties of naturally occurring lithium contents in drinking water have sparked interest among researchers. In this issue, Ishii and colleagues 8 present further argument for the hypothesis that even low lithium doses-or rather, doses of lithium at a supplemental level-might have their place in suicide prevention.…”
mentioning
confidence: 99%
“…A minimum daily requirement of 1,000 µg of dissolved lithium per day for healthy adults has been postulated by Schrauzer, 14 a dosage similar or equal to environmental lithium levels ingested daily in some geographic areas. [1][2][3][4][5][6] In fact, some natural mineral waters contain even much higher levels of lithium and are consumed unsupervised every day.…”
mentioning
confidence: 99%